Challenges and Opportunities in Academic Physiatry: An Environmental Scan. (15th October 2022) - Morgenroth, David C.; Knowlton, Tiffany; Apkon, Susan; Blauwet, Cheri A.; Burns, Anthony S.; Vallejos, Cecilia Córdova; Frontera, Walter; Hearn, Sandra L.; Jayabalan, Prakash; Lim, Peter A.; Moroz, Alex; Perret, Danielle; et al.
Abstract: Environmental scans determine trends in an organization's or field's internal and external environment. The results can help shape goals, inform strategic decision making, and direct future actions. The Association of Academic Physiatrists convened a strategic planning group in 2020, composed of physiatrists representing a diversity of professional roles, career stages, race and ethnicity, gender, disability status, and geographic areas of practice. This strategic planning group performed an environmental scan to assess the forces, trends, challenges, and opportunities affecting both the Association of Academic Physiatrists and the entire field of academic physiatry (also known as physical medicine and rehabilitation, physical and rehabilitation medicine, and rehabilitation medicine). This article presents aspects of the environmental scan thought to be most pertinent to the field of academic physiatry organized within the following five themes: (1) Macro/Societal Trends, (2) Technological Advancements, (3) Diversity and Global Outreach, (4) Economy, and (5) Education/Learning Environment. The challenges and opportunities presented here can provide a roadmap for the field to thrive within the complex and evolving healthcare systems in the United States and globally.